Learned phenotypes emerge during social stress modifying hippocampal orexin receptor gene expression - Jazmine D. W. Yaeger; Justin K. Achua; Clarissa D. Booth; Delan Khalid; Megan M. John; Leighton J. Ledesma; Trent L. Greschke; Ashley M. Potter; Chase B. Howe; Kevin T. Krupp; Justin P. Smith; Patrick J. Ronan; et al. (Scientific Reports)
Abstract Psychological distress, including anxiety or mood disorders, emanates from the onset of chronic/unpredictable stressful events. Symptoms in the form of maladaptive behaviors are learned and difficult to treat. While the origin of stress-induced disorders seems to be where learning and stress intersect, this relationship and molecular pathways involved remain largely unresolved. The hippocampus, studied for its role in learning, is divided into regions that designate the passage of neuronal signaling during memory formation, including dentate gyrus (DG), CA3, CA2, and CA1. Inputs into these hippocampal subregions, like those from hypothalamic orexinergic neurons, may modify learning outcomes. We have previously shown the orexin system to balance stress states, where receptor subtypes prompt opposing actions on behavior. Here, we explore the connection between hippocampal orexin receptors and learning during stress. In a social stress/learning paradigm separating mice into stress resilient and vulnerable populations, hippocampal Orx1R and Orx2R transcription is regulated in a phenotype-dependent fashion. We further identified Orx1R as highly expressed in the hilus of DG, while Orx2R is abundant in CA2. Finally, we designed an experiment where mice were provided prior exposure to a stressful environment, which ultimately modified behavior, as well as transcription of hippocampal orexin receptors.